A robust immobilization strategy in the nano-dispersed Ziegler–Natta catalyst: non-covalent O–Ti coordination. Issue 74 (11th August 2020) - Li, Wei; Wang, Ning; Cao, Yu; Tang, Xin; Dong, Chuanding
Abstract : A robust non-covalent O–Ti bond facilitates the synthesis of polyethylene with a narrow distribution. Abstract : An immobilization strategy of catalytic TiCl4 on polyhedral oligomeric silsesquioxanes (POSSs) is developed, which features both robustness and equivalence of active sites in ethylene polymerization thanks to the non-covalent O–Ti coordination. The symmetric structure of POSS homogenizes the coordination of the TiCl4 molecules, enabling considerable activity in the synthesis of narrowly distributed polyethylene.